Keefektifan Metode Reciprocal Teaching Pada Kemampuan Membaca Mahasiswa Di Program Studi D-IV Administrasi Bisnis Terapan - Sari, Hindri Febri Ana (P3M POLITEKNIK NEGERI AMBON, 2023)
Reading skill is one of the abilities that must be mastered by students in the D-IV Study Program Applied Business Administration. This study aims to identify the effectiveness of the Reciprocal Teaching learning model in students' reading comprehension ability in reading class. This type of research is experimental (Two group pre-test, post-test). The study population was 40 students divided into 20 experimental and 20 control classes. The data were analyzed by using t-test analysis. The results of the data analysis showed that t-count 3.47 > t-test 2.02 at a significance of 0.05. The results showed that the Reciprocal Teaching learning model effectively improved students' reading comprehension.Keywords: Reciprocal Teaching, Reading Comprehension